Achieving stable operation and shortcut nitrogen removal in a long-term operated aerobic forward osmosis membrane bioreactor (FOMBR) for treating municipal wastewater. (December 2020) - Ab Hamid, Nur Hafizah; Wang, David K.; Smart, Simon; Ye, Liu
Abstract: Forward osmosis membrane bioreactor (FOMBR) is an integrated physical-biological treatment process that has received increased awareness in treating municipal wastewater for its potential to produce high effluent quality coupled with its low propensity for fouling formation. However, reverse salt diffusion (RSD) is a major issue and so far limited studies have reported long-term FOMBR operation under the elevated salinity conditions induced by RSD. This study investigated the performance of a FOMBR in treating municipal wastewater under a controlled saline environment (6–8 g L −1 NaCl) using two separate sodium chloride draw solution (NaCl DS) concentrations (35 and 70 g L −1 ) over 243 days. At 35 g L −1 NaCl DS, the water flux performance dropped from 6.75 L m −2 h −1 (LMH) to 2.07 LMH after 72 days of operation in the first experimental stage, when no cleaning procedure was implemented. In the subsequent stage, the DS concentration was increased to 70 g L −1 and a weekly physical cleaning regime introduced. Under stable operation, the water flux performance recovery was 67% after 21 cycles of physical cleaning. For the first time in FOMBR studies, a shortcut nitrogen removal via the nitrite pathway was also achieved under the elevated salinity conditions. At the end of operation (day 243), the ammonia-oxidising bacteria ( Nitrosomonas sp.) was the only nitrifier species in the system and no nitrite oxidising bacteria was detected. The above study proves that a FOMBR system is a feasible process for treating municipal wastewater. Graphical abstract: Image 1 Highlights: 99% nitrite accumulation was facilitated by optimising the reverse salt diffusion. Nitrosomonas sp. was the only detected nitrifier in the system on day 243. FOMBR achieved >97% nutrients removal efficiency over 171 days of operation. Under long-term operation, physical cleaning recovered 67% of water flux. Structural deterioration of CTA membrane was observed in the long-term operation.